Environmental Response of Dinoponera lucida Emery 1901 (Hymenoptera: Formicidae), an Endemic Threatened Species of the Atlantic Forest Central Corridor - Simon, Soares; Schoereder, José Henrique; Teixeira, Marcos Da Cunha (Sociobiology (Chico, CA), 2020)
Endemic species of Atlantic Forest Central Corridor may have evolved under adverse climate conditions, but their response to modern climate change is unclear. The aim of this study is to evaluate the response of the endemic and endangered ant species Dinoponera lucida to biotics and abiotics factors based on three scales: ecological factors inside forest fragment, physical attributes of landscape and climatic variables of the assessed region. Data collection took place in a representative selection of forest fragments in the region where the species is distributed in. Pitfalls were used to collect samples and to assure the presence and absence of the species in the site. We also checked the abundance of food resources and applied a hemispherical photography technique to measure shading inside the fragment, in loco. Landscape attributes data and climatic predictors were collected through geoprocessing techniques. All predictors were associated with binary “presence” and “absence” data based applied in logistic models. There was no significant response to environmental aspects within the fragment or to landscape, but there was strong and peculiar response to climatic variables such as temperature and rainfall. Accordingly, D. lucida presents a restricted realized niche, a feature shared among many endangered species that can disappear due to displacement and to habitat loss caused by climate and environmental changes. This species presents all the criteria necessary to be considered as rare, which is a controversial subject with political implications for Espírito Santo state, and makes D. lucida the ideal target for urgent conservation strategies.